The Cambridge French-English thesaurus. - Lamy, Marie-Noëlle (Cambridge University Press, 1998)
Aimed at English-speaking learners and users of French at an intermediate to advanced level, this bilingual thesaurus is arranged thematically. Each category includes sayings, proverbs, quotations or usage notes connected with the topic.